An Experimental Charge Density Study of Two Isomers of Hexasilabenzene1. Issue 16 (14th March 2013) - Kratzert, Daniel; Leusser, Dirk; Holstein, Julian J.; Dittrich, Birger; Abersfelder, Kai; Scheschkewitz, David; Stalke, Dietmar
<x xml:space="preserve">Abstract</x> The aromaticity of the ring and cage isomer of a hexasilabenzene derivative was investigated by experimentally determined charge‐density distribution. Topological analysis and valence‐shell charge concentrations reflect the degree of delocalization in the various bonds. A transannular Si0–SiI bond was found in the ring conformer, while an interstitial Si0–Si0 bond along the hub in the silapropellane moiety of the cage conformer was not detected.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>